Communicational Aspects of the Symphonic Music of Carl Nielsen : How does a contemporary audience respond to Carl Nielsen's Symphony No. 2 after receiving "an elementary introduction?" - Larsen, Peter Ettrup (Taideyliopiston Sibelius-Akatemia, 2015)
In 1931, Danish composer Carl Nielsen made the following seminal statement to the newspaper Berlingske Tidende: "It's a fact that quite a few people stay away from music because they think they don't really understand its essence. And yet in reality it's so obvious that all it takes is an elementary introduction for the ear to be tuned in and thus opened to all the beauty of music". In order to test "Carl Nielsen's Communicational Condition" as the above comes to be identified, a descriptive design is used to document how a contemporary audience relatively unfamiliar with Carl Nielsen's music will respond after having been provided an elementary introduction to his Symphony No. 2 ("The Four Temperaments"). In connection with a performance of this work given by the University of Wyoming Symphony Orchestra, an empiric study of audience receptivity is undertaken. A mixed-measure approach is utilized, whereby both a quantitative survey of the attending audience and a semi-structured qualitative study with a group of local high school students are employed. Carl Nielsen's intentions concerning form and content of any desired introductory remarks are explored with the aid of classical rhetorical theory together with the author's theory of Communicational Musical Elements (CMEs) in the context of his music. Over the course of the study, the author assumes three juxtaposed roles: Researcher, Conductor, as well as Communicating Conductor, with the latter conveying the "elementary introduction" of which Carl Nielsen speaks. An argument is proffered that this particular tri-partition of roles serves as the most favorable design for embodying the guidelines specified by Carl Nielsen in his Communicational Condition. Findings of this study – that 82.2% of respondents are positive towards the idea of hearing the symphony again and as many as 98.9% of the respondents are not explicitly opposed to hearing other works by Carl Nielsen – lead to the conclusion that his music, when introduced in accordance with Carl Nielsen's Communicational Condition, resonates significantly with the present day time spirit.
Keywords: Nielsen, Carl. Sinfoniat, nro 2, op16.; viestintä; musiikki; vuorovaikutus; DocMus